3D Printing in Online Education - Zavolodko, H.; Haidar, N. (My University, 2020)
The review object is the subsystem verification and printing 3D-model online learning system mixed type. To do this, a review of analogues, technologies, stages of printing were identified. The aim is to design with IP topics that uses the additive technologies in the educational process. In the given IDEF – diagram describing the function of the system; authentication rules, verification of 3D-models, sending the model to print, selecting a device online, and basic screen forms.
Keywords: additive technologies; blended learning; 3D model; 3D printing; rules database; database